2021
DOI: 10.1108/ijoa-04-2020-2121
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable business practices and challenges in Asia: a systematic review

Abstract: Purpose This study aims to review and analyze sustainable business practices prevailing in different emerging countries in Asia. It also identifies the challenges faced by these countries in the implementation of sustainable practices. Design/methodology/approach To achieve the objectives of the study and answer the key research questions, systematic literature review method was chosen. A total of 75 papers were chosen and reviewed for this study. Findings Organizations in many emerging Asian countries are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…Bag et al ( 2018 ) suggested that corporate culture should be formed through multiple-step processes that start from the definition of business priorities and encompass the formation of employees’ behaviour, the implementation of effective, innovative activities, and the involvement of all stakeholders in the sphere of innovative entrepreneurship. Stakeholder engagement especially facilitates business model innovation and co-creation by enabling production and knowledge collection (Akbar & Ahsan, 2020 ; Brand & Blok, 2019 ; Huq et al, 2014 , 2016 ; Lathabhavan, 2021 ; Li et al, 2014 , 2020b ; Nayak et al, 2019 ; Venkatesh et al, 2021 ).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Bag et al ( 2018 ) suggested that corporate culture should be formed through multiple-step processes that start from the definition of business priorities and encompass the formation of employees’ behaviour, the implementation of effective, innovative activities, and the involvement of all stakeholders in the sphere of innovative entrepreneurship. Stakeholder engagement especially facilitates business model innovation and co-creation by enabling production and knowledge collection (Akbar & Ahsan, 2020 ; Brand & Blok, 2019 ; Huq et al, 2014 , 2016 ; Lathabhavan, 2021 ; Li et al, 2014 , 2020b ; Nayak et al, 2019 ; Venkatesh et al, 2021 ).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…They can be used by local authorities, government agencies, and civil society organizations, and among high, medium, and low-income countries. The SDGs can also guide corporate behaviour, and the relationship between the SDGs and CSR has already been a topic in many studies (Martinuzzi et al , 2017; Macellari et al , 2018; Bag and Pretorius, 2020; Lathabhavan, 2021). Furthermore, Van Zanten and Van Tulder stated that the SDGs provide the foundational platform and “central and lasting framework” for companies to target global sustainability goals (van Zanten and van Tulder, 2018, p. 227).…”
Section: Literature Reviewmentioning
confidence: 99%
“…So, to grab this market opportunity, the firms also need to implement some changes like new product development, market development, market extension, diversification, product redesign or changes in the marketing policies (Ovharhe, Woko & Ogolo, 2021). The enterprises, implementing green practices are in the business of generating profit at their merchandizing operations (Lathabhavan, 2021).…”
Section: Green Entrepreneurshipmentioning
confidence: 99%